The Role of Ascitic Paracentesis in Liver Cirrhosis in Improving the Function and Structure of the Heart - Juwita Sembiring; Tehar Karo-Karo; Lufti Latif; Lukman Hakim Zain; Pangarapen Tarigan (The Indonesian Society for Digestive Endoscopy, 2003)
Background: Heart abnormalities in cirrhotic patients have been known for five decades, with atria and ventricular dilatation. Pozzi et al reported that in cirrhotic patients with or without ascites, the diastolic function was lower than control. Ascitic paracentesis improved diastolic function. The diameter of both atria was larger in cirrhotic patients with or without ascites. The diastolic diameter of left ventricle did not differ significantly in cirrhotic patients with or without ascites compared to control, but there was an increase after paracentesis. Ejection fraction was lower in cirrhotic and increased after ascitic parancentesis although the increase was not significant. The aim of the Study: To compare the function and structure of the heart before and after ascitic paracentesis in cirrhotic patients. Methods: This study took place from February 2000 to April 2001 in dr. Pringadi Hospital/H.Adam Malik Hospital. There were 18 samples (12 men and 6 women), 15 of which were cirrhotic patients with tense ascites and 3 cirrhotic patients with refractory ascites. The mean age was 51,8 + 8,28 years, the youngest being 29 years and the oldest 65 years. The mean ascitic fluid removed by paracentesis was 7,20 liters with a range of 5 to 9 liters. Immediately following paracentesis, Dextran 40 % was administered at a dose of 8g/ 1L ascitic fluid aspirated. Results: The diameter of the four heart chambers decreased after paracentesis, but the decrease was not statistically significant. There was increase in E/A ratio after ascitic paracentesis, from 0,93 + 0,370 to 1,06 + 0,383 (significant, p0,05), meaning that there was an improvement in diastolic function after ascitic paracentesis. There was also an increase in ejection fraction from 68,99 + 13,26 % to 72,10 + 11,10 %, but this was not significant (p0,05). Conclusion: After paracentesis, there was a significant improvement in diastolic function while the diameter of the four heart chambers decreased and the ejection fraction increased insignificantly. Keywords: Ascitic paracentesis - liver cirrhosis - heart function and structure.